2016
DOI: 10.1136/archdischild-2016-310647
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a novel adaptive algorithm for automated control of oxygen therapy in preterm infants on non-invasive respiratory support

Abstract: The novel PID algorithm was very effective for automated oxygen control in preterm infants, and deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 28 publications
1
62
9
Order By: Relevance
“…In our study, 37–43% of preterm and/or LBW neonates were above the target at all time points, higher than one study (25%),22 but lower than two others (55–58%) 19, 21. Notably, only one of these studies was conducted in an LMIC.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In our study, 37–43% of preterm and/or LBW neonates were above the target at all time points, higher than one study (25%),22 but lower than two others (55–58%) 19, 21. Notably, only one of these studies was conducted in an LMIC.…”
Section: Discussioncontrasting
confidence: 63%
“…All studies except one were conducted in high‐income settings. These studies showed that, with manual titration, SpO 2 was outside and/or above the target range 18–84% and 15–58% of time, respectively 15, 16, 17, 18, 19, 20, 21, 22, 25, 26. In Colombia, SpO 2 was within or above the target 34 and 55% of the time, respectively 21.…”
mentioning
confidence: 98%
“…Whether such a simulation can reliably predict the function of an algorithm when directly applied to preterm infants will need further investigation. However, using data from our initial clinical study,26 the assumptions regarding the blend of ratio and shunt were found to produce an SpO 2 targeting profile in simulation that closely matched actual data during automated oxygen control (see online supplement). Refinement of physiological modelling, possibly including multiple compartments with variable blood flow,36 may further improve the authenticity of the simulation.…”
Section: Discussionmentioning
confidence: 83%
“…For the purpose of preclinical and ultimately initial clinical testing26 the algorithm was housed in a stand-alone device consisting of a processing platform (laptop computer), device inputs and outputs, a servo-controlled air–oxygen blender and a user interface displayed on the computer screen. The algorithm code was written in a graphical programming language (LabVIEW 2010, National Instruments, Austin, Texas, USA) and uploaded in the laptop computer.…”
Section: Methodsmentioning
confidence: 99%
“…A group from Tasmania reports on their contribution to this field 3 4. They developed an FiO 2 controller based on a PID algorithm that was designed to avoid hyperoxaemia and adapt to the presence of severe V/Q mismatch.…”
mentioning
confidence: 99%